THE IMPACT OF TELEMEDICINE PLATFORMS ON HEALTHCARE IN RURAL AREAS - Valijon Maxsudov; Fazliddin Arzikulov; Dilnaz Eshimova (Modern American Journals, 2025)
This paper explores the impact of telemedicine platforms on healthcare delivery in rural areas. It highlights how digital health technologies help bridge the gap caused by geographic isolation, lack of medical professionals, and inadequate infrastructure. Key benefits of telemedicine include improved access to healthcare services, cost reduction, and better disease management. However, challenges such as poor internet connectivity, low digital literacy, and regulatory barriers remain significant obstacles. The study concludes that with strategic investments in infrastructure, training, and supportive policies, telemedicine can play a transformative role in achieving equitable healthcare for rural populations.
Keywords: Telemedicine, rural healthcare, digital health, health access, remote consultations, healthcare equity, mhealth, telehealth platforms, digital divide, health technology.